MALNUTRITION AND COMORBIDITY PATTERN AMONG UNDER FIVE CHILDREN IN URBAN SLUMS OF BERHAMPUR: A CROSS-SECTIONAL STUDY - NANDA, NARAYAN PRASAD; NAYAK, LOMAPADA; SAHOO, SANJAYA KUMAR; KARMEE, NIVEDITA; SATAPATHY, DURGA MADHAB (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: Nutritional status of under five children is a matter of concern worldwide and malnutrition is one of the most important public health problems. The children of urban slums carry relatively more risk due to their epidemiological profile, exposure to infectious agents and lifestyle-related risk factors, and culture-based health beliefs. To access the nutritional status and associated comorbidities among under five children in the urban slums of Berhampur. Methods: A cross-sectional community-based study was carried out among 385 children between 6 and 59 months of age residing in the urban slum areas of Berhampur Odisha. Out of total 174 slums, 20% (35) were selected randomly and from each of these 35 slums, 11 children were selected. The assessment of the nutritional status of the child was done using the World Health Organization, weight for age (WFA), weight for height (WFH), height for age (HFA), and MUAC and general physical examination. Results: In our study, the prevalence of underweight (low WFA), stunting (low HFA), and wasting (low WFH) was 152 (39.48%), 160 (41.43%), and 144 (37.20%), respectively. No children were observed with overweight or obesity. The prevalence of ARI, diarrhoea, worm infestation, skin diseases, dental problems, ear and eye infections, and injury were 32.98%, 13.77%, 9.61%, 4.67%, 4.41%, 2.86%, and 1.03%, respectively. Conclusion: It was observed that the prevalence of undernutrition was more than the state average but overnutrition was absent in our study area. Regarding the comorbid conditions, nearly one-third of the children had anemia and RTI, both were significantly associated with malnutrition.